Operation Save the World from Adverse Drug Reactions: findings from a drug safety surveillance programme in Nigeria - Yohanna Kambai Avong, MPH; Bolajoko Jatau, MPH; Gbenga Ayodele Kayode, PhD; Blessing Ukpabi, MSc; Eunice Bosede Avong, MPH; James Okuma, MS; Dennis Mordi, MSc; Alash'le Abimiku, PhD; Obinna Ogbanufe, MPH; Charles Olalekan Mensah, MBA; Patrick Dakum, MPH (Elsevier, 2019)
Background: Adverse drug reactions are an important causes of death and account for 5-35% of hospital admissions. Operation Save the World from Adverse Drug Reactions is a drug safety surveillance programme developed in 2005 by the Institute of Human Virology Nigeria (IHVN) to address the under-reporting of adverse drug reaction in Nigeria, where millions of people use antiretroviral, anti-tuberculosis, and anti-malaria drugs. The drug safety surveillance programme runs in major public hospitals but is managed by the National Pharmacovigilance Center in collaboration with IHVN. The goal is to ensure public and global health, while the primary outcome is the reporting of adverse drug reactions to the Uppsala Monitoring Centre, through the Nigerian National Agency for Food and Drug Administration and Control (NAFDAC). Pharmacovigilance training and the publishing of papers are secondary outcomes. Methods: The drug safety surveillance programme in Nigeria combines six key activities: collaboration between government and the private sector; the training of medical doctors, pharmacists, and nurses; establishment of pharmacovigilance centres in public hospitals; development of platforms for submitting individual case safety reports; the publishing of peer-review articles; and submission of individual case safety reports. To ensure sustainability, we collaborated with the Nigerian Government and research institutions, and trained only government health-care workers, who were randomly selected from a pool of applicants that applied to advertisements in three national newspapers. Findings: Between 2004 and 2016, Nigeria's National Pharmacovigilance Center received 16 500 individual case safety reports out of 80 000 adverse drug reaction reporting forms. The number of health-care workers who were trained in the reporting of adverse drug reactions was fewer than 300 and there was no training model during this time. However, between 2014 and 2018 when Operation Save the World from Adverse Drug Reactions was introduced and implemented, more than 5000 individual case safety reports, with more than 40 000 reactions were submitted. Furthermore, more than 3000 health-care workers have been trained in the reporting of adverse drug reactions, and a Structured Pharmacovigilance and Training Initiative (SPHARTI) model has been developed, with two peer-reviewed articles published. Serious adverse drug reactions, such as bilateral gynaecomastia, violent psychiatric disorders, and Stevens-Johnson syndrome have also been reported. Interpretation: The drug safety surveillance programme Operation Save the World from Adverse Drug Reactions has increased the reporting of adverse drug reactions in Nigeria and increased the critical mass of qualified health-care workers trained in the reporting of adverse drug reactions. The strength of the programme is in the combination of the six key activities. Challenges remain in establishing causality of the reported reactions and operating the programme at primary health centres. Funding: US PEPFAR.